2013
DOI: 10.1021/jo401796g
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Catalyzed Benzylic Fluorination as a Synthetic Equivalent to 1,4-Conjugate Addition of Fluoride

Abstract: We explore in detail the iron-catalyzed benzylic fluorination of substrates containing aromatic rings and electron-withdrawing groups positioned β to one another, thus providing direct access to β-fluorinated adducts. This operationally convenient process can be thought of not only as a contribution to the timely problem of benzylic fluorination but also as a functional equivalent to a conjugate addition of fluoride, furnishing products in moderate to good yields and in excellent selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 44 publications
(30 reference statements)
0
30
0
Order By: Relevance
“…For example, the incorporation of a single fluorine atom at the β‐position has been shown to influence the conformational integrity of cyclic amines and amides,9 prevent mitochondrial β‐oxidation of fatty acids,10 and serve as an adequate positron emission tomography (PET) probe for elucidating a number of biosynthetic and metabolic pathways 11. Consequently, a number of methods have emerged pertaining to the targeted synthesis of β‐fluorinated carbonyl compounds 1c,f,g. 12, 13 It stands to reason that the development of an alternative, photocatalytic route to β‐fluorides from cyclopropanols would be highly desirable, providing a much needed tool in the armamentarium of the medicinal chemist.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the incorporation of a single fluorine atom at the β‐position has been shown to influence the conformational integrity of cyclic amines and amides,9 prevent mitochondrial β‐oxidation of fatty acids,10 and serve as an adequate positron emission tomography (PET) probe for elucidating a number of biosynthetic and metabolic pathways 11. Consequently, a number of methods have emerged pertaining to the targeted synthesis of β‐fluorinated carbonyl compounds 1c,f,g. 12, 13 It stands to reason that the development of an alternative, photocatalytic route to β‐fluorides from cyclopropanols would be highly desirable, providing a much needed tool in the armamentarium of the medicinal chemist.…”
Section: Methodsmentioning
confidence: 99%
“…However, only in recent years has benzylic fluorination started to gain increased attention, proving to be a powerful tool for site-specific C(sp 3 )-F bond formation. 93,[104][105][106][107][108][109][110][111][112][113][114] Generally, amongst these studies, different fluorination routes can be identified: (i) electrophilic fluorination employing Selectfluor®, N-fluoropiridinium salts and NFSI as fluorinating sources, 93,[104][105][106][107] (ii) nucleophilic fluorination with triethylamine trihydrofluoride, TREAT•HF, and fluor-ide salts, 108,109 and (iii) thermal-or photocatalysed radical fluorination. [110][111][112][113] Amongst these, benzylic fluorination catalysed by transition metal complexes using electrophilic fluorinating reagents represents the most exploited (see examples in Scheme 10, entries 1-3).…”
Section: Benzylic Fluorinationmentioning
confidence: 99%
“…[110][111][112][113] Amongst these, benzylic fluorination catalysed by transition metal complexes using electrophilic fluorinating reagents represents the most exploited (see examples in Scheme 10, entries 1-3). 93,[104][105][106][107] Despite the difficulties associated with the activation of C-H bonds, which may require stronger reaction conditions i.e. more powerful oxidants or radical initiators, than those typically used for pre-activated substrates such as carboxylic acids, moderate TONs (up to 10) have been achieved via this route.…”
Section: Benzylic Fluorinationmentioning
confidence: 99%
“…29) Lectka applied substoichiometric amounts of an iron(II) complex to enable a simple and selective benzylic C-H bond fluorination protocol, with Selectfluor in acetonitrile at room temperature (Fig. 30) [58,59]. In 2014, Tang and coworkers reported a silver(I)-catalyzed difluorination of benzylic methylene groups (Fig.…”
Section: Fluorination Of C-h Bondsmentioning
confidence: 99%